Teachers’ views of boys and girls as readers in the English language - Mohd. Asraf, Ratnawati; Abdullah, Hazlina (American Scientiﬁc Publishers, 2018)
Research has increasingly investigated the role of attitudes toward reading and language learning, and how it might be different in boys and girls. This paper reports on an investigation of Malaysian elementary school students’ attitudes toward reading in the English language as perceived by their teachers. In-depth information of teachers’ personal practices in teaching reading to the students, their ways of dealing with them, and their suggestions on the teaching of boys and girls were obtained through focus group interviews as well as journal entries. As manifested in the results of the interviews, the teachers felt that among the students that they taught, the boys and girls had different attitudes toward reading and that the girls generally did better than boys in the English class. However, the teachers also felt that boys from good classes seemed to have more positive attitudes toward reading in English.